1997
DOI: 10.1200/jco.1997.15.3.1218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of therapy with epoetin alfa on clinical outcomes in patients with nonmyeloid malignancies during cancer chemotherapy in community oncology practice. Procrit Study Group.

Abstract: Epoetin alfa is effective in improving the functional status and quality of life in anemic cancer patients receiving chemotherapy, as well as increasing hemoglobin level and decreasing transfusion requirements. Improvement in functional status can be attributed to an increase in hemoglobin level, demonstrating that quality of life in this group of patients can be improved by aggressively treating anemia. Further studies will be required to define the optimal doses and schedules for epoetin alfa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
405
6
12

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 650 publications
(459 citation statements)
references
References 22 publications
36
405
6
12
Order By: Relevance
“…However, the relation between FACT-F scores, particularly the reduction in fatigue, and haemoglobin concentration seen here is consistent with other reports that have found improved alleviation of patient-reported symptoms of anaemia with increasing haemoglobin levels (Glaspy et al, 1997;Gabrilove et al, 2001). Confirmatory studies are needed to investigate whether the observed increases in haemoglobin translate into reductions in transfusion requirements and/or improvements in HRQOL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the relation between FACT-F scores, particularly the reduction in fatigue, and haemoglobin concentration seen here is consistent with other reports that have found improved alleviation of patient-reported symptoms of anaemia with increasing haemoglobin levels (Glaspy et al, 1997;Gabrilove et al, 2001). Confirmatory studies are needed to investigate whether the observed increases in haemoglobin translate into reductions in transfusion requirements and/or improvements in HRQOL.…”
Section: Discussionsupporting
confidence: 90%
“…The eligibility criteria minimised the entry of patients with any significant transfusion requirement, probably reducing the number of transfusions over the course of the 12-week study period as well, and consequently minimising differences between the placebo and treatment groups. The transfusion rates in the darbepoetin alpha groups are generally similar to those reported in the literature for patients treated with rHuEPO (Glaspy et al, 1997;Demetri et al, 1998;Littlewood et al, 2001;Quirt et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…In an open-label study, in which rHuEPO was administered to 2342 patients receiving cytotoxic chemotherapy, patients' mean energy levels increased by 38%, activity increased by 32%, and overall QOL increased by 24% after 4 months of therapy, all significant increases (P < 0.001) (Glaspy et al, 1997). A later study involving 2370 patients reported similar results, noting that increased haemoglobin values from baseline were associated with improved activity level, energy, and overall well-being (Figure 1).…”
Section: Improved Quality Of Lifementioning
confidence: 99%
“…Numerous studies, both placebo-controlled and open-label, have consistently shown that increasing haemoglobin values has a measurable and significant effect on QOL parameters in cancer patients whether they are receiving (Abels, 1993;Case et al, 1993;Henry and Abels, 1994;Leitgeb et al, 1994;Glaspy et al, 1997;Demetri et al, 1998) or not receiving concurrent chemotherapy (Ludwig et al, 1995). In all of these studies, haemoglobin was increased by the administration of recombinant human erythropoietin (rHuEPO, epoetin alfa).…”
Section: Improved Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation